Enantioselective Addition of a 2‐Alkoxycarbonyl‐1, 3‐dithiane to Imines Catalyzed by a Bis(guanidino)iminophosphorane Organosuperbase. (20th October 2015) - Kondoh, Azusa; Oishi, Masafumi; Takeda, Tadahiro; Terada, Masahiro
Abstract: A chiral bis(guanidino)iminophosphorane catalyzes enantioselective addition reactions of a 1, 3‐dithiane derivative as a pronucleophile. The chiral uncharged organosuperbase facilitates the addition of benzyloxycarbonyl‐1, 3‐dithiane to aromatic N ‐Boc‐protected imines to provide optically active α‐amino‐1, 3‐dithiane derivatives, which are valuable versatile building blocks in organic synthesis. Abstract : Eine chirale Organosuperbase katalysiert enantioselektive Additionen von 2‐Alkoxycarbonyl‐1, 3‐dithian: Der chirale, neutrale Bis(guanidino)iminophosphoran‐Katalysator ermöglicht die Reaktion mit aromatischen, N‐Boc‐geschützten Iminen, wodurch optisch aktive α‐Amino‐1, 3‐dithiane erhalten werden, die wertvolle und vielfältige Intermediate in der organischen Synthese darstellen.